Inflammation and physical dysfunction: responses to moderate intensity exercise in chronic kidney disease. Issue 5 (22nd November 2021) - Watson, Emma L; Baker, Luke A; Wilkinson, Tom J; Gould, Doug W; Xenophontos, Soteris; Graham-Brown, Matthew; Major, Rupert W; Ashford, Robert U; Viana, Joao L; Smith, Alice C
ABSTRACT: Background: People with chronic kidney disease (CKD) experience skeletal muscle wasting, reduced levels of physical function and performance, and chronic systemic inflammation. While it is known that a relationship exists between inflammation and muscle wasting, the association between inflammation and physical function or performance in CKD has not been well studied. Exercise has anti-inflammatory effects, but little is known regarding the effect of moderate intensity exercise. This study aimed to (i) compare systemic and intramuscular inflammation between CKD stage G3b–5 and non-CKD controls; (ii) establish whether a relationship exists between physical performance, exercise capacity and inflammation in CKD; (iii) determine changes in systemic and intramuscular inflammation following 12 weeks of exercise; and (iv) investigate whether improving inflammatory status via training contributes to improvements in physical performance and muscle mass. Methods: This is a secondary analysis of previously collected data. CKD patients stages G3b–5 ( n = 84, n = 43 males) and non-CKD controls ( n = 26, n = 17 males) underwent tests of physical performance, exercise capacity, muscle strength and muscle size. In addition, a subgroup of CKD participants underwent 12 weeks of exercise training, randomized to aerobic (AE, n = 21) or combined (CE, n = 20) training. Plasma and intramuscular inflammation and myostatin were measured at rest and following exercise. Results: Tumour necrosis factor-α was negatively associated with lower ^^^.V O2Peak (P = 0.01), Rectus femoris-cross sectional area (P = 0.002) and incremental shuttle walk test performance (P < 0.001). Interleukin-6 was negatively associated with sit-to-stand 60 performances (P = 0.006) and hand grip strength (P = 0.001). Unaccustomed exercise created an intramuscular inflammatory response that was attenuated following 12 weeks of training. Exercise training did not reduce systemic inflammation, but AE training did significantly reduce mature myostatin levels (P = 0.02). Changes in inflammation were not associated with changes in physical performance. Conclusions: Systemic inflammation may contribute to reduced physical function in CKD. Twelve weeks of exercise training was unable to reduce the level of chronic systemic inflammation in these patients, but did reduce plasma myostatin concentrations. Further research is required to further investigate this.